Long-Term Postoperative Total Knee Arthroplasty Flexion Scores in Relation to Body Mass Index - Siegel, Matthew A.; Patetta, Michael J.; Fuentes, Angie M.; Haleem, Armaan S.; Forsthoefel, Craig W.; Sood, Anshum; Gonzalez, Mark H. (The Journal of Knee Surgery, 2020)
Knee range of motion (ROM) is an important postoperative measure of total knee arthroplasty (TKA). There is conflicting literature whether patients who are obese have worse absolute ROM outcomes than patients who are not obese. This study analyzed whether preoperative body mass index (BMI) influences knee ROM after patients' primary TKA. A retrospective investigation was performed on patients, who underwent primary TKA at an academic institution, by one of three fellowship-trained adult reconstruction surgeons. Patients were stratified according to their preoperative BMI into nonobese (BMI < 30.0 kg/m2) and obese (BMI ≥ 30.0 kg/m2) classifications. Passive ROM was assessed preoperatively as well as postoperatively at patients' most recent follow-up visit that was greater than 2 years. Mann–Whitney U tests were performed to determine statistical significance at p-value <0.05 for ROM outcomes. No statistically significant differences were observed when ROM in the nonobese group was compared with ROM in the obese group both preoperatively (105.73 ± 11.58 vs. 104.14 ± 13.58 degrees, p-value = 0.417) and postoperatively (105.83 ± 14.19 vs. 104.49 ± 13.52 degrees, p-value = 0.777). Mean follow-up time for all patients was 4.49 ± 1.92 years. In conclusion, long-term postoperative ROM outcomes were similar between patients who were nonobese and patients who were obese.
Keywords: body mass index; range of motion; obesity; total knee arthroplasty; joint replacement